Overcoming Content-Associated Challenges Using Attention-Focused Methods (Journal on Excellence in College Teaching, 2024)
A common challenge in higher education is teaching required content for which students traditionally have lower levels of interest. Physical therapist education programs experience this challenge when training entry-level students to document in the medical record. The authors compared learning outcomes among physical therapy students taught documentation skills through traditional methods with those learning via an alternative format designed to maximize their focus and attention. Outcomes suggest that the attention-focused approach engaged students and better prepared them to use learned skills in clinical practice. Faculty from other disciplines may benefit from using similar approaches when teaching traditionally difficult content.